Quality and postharvest physiology of "Nopalitos" and "Tunas" - Cantwell, Marita (Journal of the Professional Association for Cactus Development, 2021)
Tue objective of this paper is to provide an overview of quality and postharvest aspects of "Tunas" (fruits) and "Nopalitos" (vegetables) produced by the Prickly pear Cactus (Opuntia spp.).